Chemically Etched 3D-Printed Optical Fibers for Biocompatible Applications (Journal of Medical Device Technology, 2025)
Hydrogel coatings enhance the biocompatibility of optical fibers by reducing mechanical mismatch with tissue, with chemical etching as a critical first step to improve coating adhesion. However, the effects of sodium hydroxide etching on 3D-printed fibers remain understudied. Polyethylene terephthalate glycol (PETG) has shown great promise in advancing 3D printing technology for optical fiber fabrication due to its low optical loss, printability, and chemical resistance. In this study, PETG optical fibers were etched in 0.1 mM and 1 mM NaOH for 30–120 minutes and evaluated for optical loss, morphology, and chemical structure. All fibers maintained low optical loss, with a maximum of 0.18 dB/cm after 2 hours in 1 mM NaOH. No visible degradation or discoloration was observed, and FTIR analysis showed no structural changes at =C–H, CH₂, C–O–C, C=O, and C–H stretching, confirming no degradation at structural level which could compromise the biocompatibility of PETG. These results confirm that mild chemical etching does not compromise the optical or chemical integrity of PETG fibers, supporting their suitability for biocompatible, hydrogel-coated optical systems in biomedical applications.
Keywords: Optical fiber; 3D printing; 3D printed optical fiber